Higher avian biodiversity, increased shrub cover and proximity to continuous forest may reduce pest insect crop loss in small‐scale oil palm farming - Yahya, Muhammad Syafiq; Ibrahim, Nor Laili; Kamarudin, Norman; Ahmad, Siti Nurulhidayah; Atikah, Sharifah Nur; Sanusi, Ruzana; Norhisham, Ahmad Razi; Mohd Masri, Mohamed Mazmira; Azhar, Badrul (John Wiley and Sons, 2024)
One of the key ecosystem services offered by avian biodiversity within agricultural landscapes is natural predation. Nonetheless, the current use of biological control agents such as farmland birds in oil palm plantations is relatively limited. This study aimed to assess the potential roles of avian biodiversity, particularly insectivores that provide natural predation against oil palm herbivorous insects. We also investigated the influence of local- and landscape-scale variables on foliage damage (crown or frond). Our data showed that crown damage decreased with increasing farmland bird richness (overall and insectivore), shrub cover, dried biomass and elevation, but increased with epiphyte cover, oil palm height and distance to continuous forest. Frond damage was negatively related to bird richness (overall, insectivore and non-insectivore) and non-insectivore abundance, elevation and shrub cover, while increased with insectivorous abundance, epiphyte cover, oil palm height and distance to continuous forest. We also found that plantations (≥50 ha) were more susceptible to foliage damage from pest insects than smallholdings (<50 ha). There was no evidence that indicate the influence of forest patches on foliage damage. Synthesis and applications. Our study highlights the economic value of conserving biodiversity, most notably, farmland birds and continuous forests with respect to biological control of defoliating pests and maintaining yield productivity in oil palm cultivation. Growers, particularly major plantation companies should make oil palm farming more biodiversity-friendly in order to increase the number of biological control agents such as birds. © 2024 The Authors. Journal of Applied Ecology © 2024 British Ecological Society.